Stability and bifurcation analysis of a prey-predator model with Smith growth rate in presence of environmental toxins - Maiti, Titli; Sarkar, Avijit (International Journal of Advanced Mathematical Sciences, 2025)
The aim of the present article is to formulate a prey-predator model by assuming that the preys inhabit in contaminated environments and undergo Smith growth rate instead of logistic growth rate. Stability and bifurcation phenomenon of the model have been analyzed with utmost care.